High-strength silk fibroin / hydroxyapatite bone repair material and preparation method thereof
By methacrylation of silk fibroin and nano-hydroxyapatite and high-temperature hot press molding, high-strength silk fibroin/hydroxyapatite bone repair material is formed, and the unsolid bonding of the organic-inorganic components is solved. The problem has significantly improved mechanical properties and biological activity and provided more effective bone defect repair materials.
Patent Information
- Application Number
- CN202411640285.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing silk fibroin/hydroxyapatite composite bone scaffolds have shortcomings in mechanical properties and osteoinducible activity, mainly due to the insolid bonding of the organic-inorganic components interface, resulting in unstable mechanical properties and poor biological activity.
By esterifying silk fibroin and nano-hydroxyapatite, covalent bonds are formed, and molding is carried out under high temperature hot pressing conditions, the interface bonding and dispersion between organic-inorganic components are improved, and high-quality components are formed Strong silk fibroin/hydroxyapatite bone repair material.
It significantly improves the mechanical properties and biocompatibility of bone repair materials, enhances bone induction activity, solves the problems of insolid interface bonding and uneven dispersion of traditional composite scaffold materials, and provides a better bone defect repair solution.
Smart Images

Figure CN119258272A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical materials, and particularly relates to a method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material. Background Art
[0002] Bone tissue has the ability to self-repair and can effectively heal small injuries. However, bone defects exceeding a critical size are difficult to heal on their own, such as large bone defects caused by traumatic injuries, degenerative diseases, congenital defects, or surgical resection of tumors. To achieve bone tissue regeneration and functional restoration, clinical intervention is usually required, such as autologous bone transplantation, allogeneic bone transplantation, or fixation using bioinert metal devices. However, these treatment options have certain limitations. Autologous bone transplantation is limited by the scarcity of donors, allogeneic bone grafts have the risk of disease transmission from the donor, and metal bone fixation devices need to be surgically removed in the later stages of treatment, which can easily cause secondary damage. To overcome these limitations, bone tissue engineering has emerged. It aims to utilize the synergistic effects of biological scaffold materials, cells, and growth factors to create artificial bones that can promote bone tissue regeneration and repair. Among them, organic-inorganic composite scaffold materials, as common composite scaffold materials for bone tissue engineering, have many excellent properties.
[0003] Silk fibroin is a natural protein extracted from silk, with good biocompatibility and diverse physical and chemical properties. Because its structure is similar to that of type I collagen, silk fibroin is considered a preferred natural polymer material in bone tissue engineering. However, bone repair materials made from pure silk fibroin have poor mechanical and osteogenic properties. To improve this shortcoming, silk fibroin is used as a matrix and hydroxyapatite is added to simulate the natural structure and properties of bone. The Chinese invention patent with publication number CN112972766B provides a silk fibroin-hydroxyapatite composite bone scaffold and its preparation method. A silk fibroin solution and a hydroxyapatite aqueous dispersion are ultrasonically treated to form a mixed solution, and a silk fibroin / hydroxyapatite composite three-dimensional porous scaffold is prepared rapidly and non-toxicly by direct current directional electric field induction. However, the silk fibroin / hydroxyapatite composite system obtained by simple physical stirring and mixing lacks a strong interface bond between the organic silk fibroin component and the inorganic hydroxyapatite component, which will cause a large amount of hydroxyapatite to agglomerate in the system and not be evenly dispersed, resulting in the scaffold's mechanical properties and osteoinductive activity being affected. The Chinese invention patent with publication number CN110522950A provides a silk fibroin / hydroxyapatite composite scaffold and its preparation method. Microwaves are used to assist the mineralization reaction of the silk fibroin scaffold immersed in SBF solution, so that hydroxyapatite is deposited on the surface and inside of the silk fibroin scaffold, thereby obtaining a silk fibroin / hydroxyapatite composite scaffold. The above patent uses substrate mineralization deposition to obtain a silk fibroin / hydroxyapatite composite scaffold. Although it will improve the interface bond between the organic silk fibroin component and the inorganic hydroxyapatite component, the content of hydroxyapatite will be limited, affecting the full bonding between the organic and inorganic components in the scaffold, resulting in problems such as low mechanical properties and weak osteoinductive activity of the scaffold, and there are certain defects when used as a bone repair material. Summary of the Invention
[0004] In response to the above problems, the present invention provides a method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material. This method introduces covalent bonds by methacrylate-esterifying silk fibroin and nano-hydroxyapatite, thereby improving the interfacial bonding ability and dispersion stability between the organic component of silk fibroin and the inorganic component of nano-hydroxyapatite. The material is then subjected to high-temperature hot pressing and molding to improve the mechanical properties and osteoinductive activity of the bone repair material, thereby solving the problem that traditional organic-inorganic bone tissue engineering composite scaffold materials have unstable mechanical properties and poor biological activity due to weak interfacial bonding of internal components.
[0005] The present invention adopts the following technical solutions: A method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material comprises mixing methacrylated silk fibroin and methacrylated nanohydroxyapatite, covalently cross-linking the two under the action of a photoinitiator, and then subjecting the mixture to high-temperature hot pressing to obtain the high-strength silk fibroin / hydroxyapatite bone repair material.
[0006] The method for preparing the above-mentioned high-strength silk fibroin / hydroxyapatite bone repair material specifically comprises the following steps: (1) Preparation of a methacrylated silk fibroin solution: After heating deionized water to boiling, anhydrous sodium carbonate and silk were added to degummed silk; after washing and drying, the dried degummed silk was dissolved in a lithium bromide solution to obtain a silk fibroin / lithium bromide mixed solution, followed by addition of glycidyl methacrylate to modify the silk fibroin in the dark for 3 hours, followed by dialysis with deionized water at room temperature in the dark for 5 days, and the dialyzed solution was centrifuged and concentrated to obtain a methacrylated silk fibroin solution. The mass fraction of the methacrylated silk fibroin solution was 15%-30%; (2) Preparation of methacrylated nanohydroxyapatite: The dehydrated nanohydroxyapatite and isophorone diisocyanate were heated and stirred in an oil bath, followed by the addition of dibutyltin dilaurate and N,N-dimethylformamide, and the reaction was carried out in a nitrogen atmosphere. 2-hydroxyethyl methacrylate was then added and continued to stir, and finally methanol was added to terminate the reaction. The precipitate was collected by centrifugation, washed with dichloromethane, dried at room temperature, and ground to obtain methacrylated nanohydroxyapatite powder. (3) Preparing a silk fibroin / hydroxyapatite crosslinking system: mixing the methacrylated silk fibroin solution obtained in step (1) with a photoinitiator, and then adding the methacrylated nanohydroxyapatite powder obtained in step (2), stirring and mixing at room temperature in the dark to obtain a precursor slurry of a bone repair material; irradiating the precursor slurry under ultraviolet light to obtain a silk fibroin / hydroxyapatite crosslinking system; (4) Preparation of high-strength silk fibroin / hydroxyapatite bone repair material: The silk fibroin / hydroxyapatite cross-linked system prepared in step (3) was freeze-dried at -80°C in a vacuum oven and then crushed and ground into powder using a high-speed crusher at a speed of 39,000 r / min. The powder was hot-pressed at a pressure of 2 MPa and a temperature of 200°C for 20 minutes to obtain a high-strength silk fibroin / hydroxyapatite bone repair material.
[0007] Furthermore, the reaction temperature for adding 2-hydroxyethyl methacrylate and continuing stirring in step (2) is 40-80°C, the reaction time is 1-5 h, and the reaction is carried out in the dark.
[0008] Furthermore, the mass fraction of the methacrylated nano-hydroxyapatite powder in the precursor slurry of the bone repair material in step (3) is 10wt%-50wt%.
[0009] Furthermore, the photoinitiator in step (3) is one of Irgacure 2959, Ruthenium Photoinitiator and phenyl-2,4,6-trimethylbenzoyl lithium hypophosphite.
[0010] Furthermore, the wavelength of the ultraviolet light in step (3) is 365 nm, and the irradiation time is 5-20 min.
[0011] A high-strength silk fibroin / hydroxyapatite bone repair material prepared by the above preparation method.
[0012] The application of the high-strength silk fibroin / hydroxyapatite bone repair material in loading drugs comprises the steps of adding the drugs into the precursor slurry of the bone repair material.
[0013] The beneficial effects of the present invention are: (1) The present invention uses a photoinitiator to induce a chemical crosslinking reaction between methacrylated silk fibroin and methacrylated nanohydroxyapatite, forming a stable covalent bond, thereby improving the organic-inorganic interface bonding and the dispersion of nanohydroxyapatite in bone repair materials. Compared with traditional organic-inorganic composite scaffolds, the present invention solves the problems of weak organic-inorganic interface bonding, uneven distribution of nanohydroxyapatite in bone repair materials, insufficient mechanical properties, and weak osteoinductive activity. It has significantly enhanced mechanical properties, good biocompatibility and degradability, and provides a solution for bone defect repair.
[0014] (2) The present invention successfully prepared methacrylated nanohydroxyapatite through a two-step process. First, isophorone diisocyanate reacts with the hydroxyl groups on the surface of the nanohydroxyapatite, fixing it on the surface of the nanohydroxyapatite and providing active sites. These sites then react with 2-hydroxyethyl methacrylate to introduce methacrylate groups, thereby enhancing the content and chemical activity of the methacrylate groups on the surface of the nanohydroxyapatite, enabling it to more fully bind to the methacrylated silk fibroin, and under the action of a photoinitiator, form a composite bone repair material with higher density and better mechanical properties.
[0015] (3) The high-strength silk fibroin / hydroxyapatite bone repair material of the present invention is prepared by hot pressing the covalently cross-linked silk fibroin / hydroxyapatite composite powder at a pressure of 2 MPa and a temperature of 200°C for 20 minutes, which is beneficial to the interface fusion between the organic component silk fibroin and the inorganic component hydroxyapatite inside the composite material, thereby forming a high-strength silk fibroin / hydroxyapatite bone repair material with a uniform and complete interface.
[0016] (4) The high-strength silk fibroin / hydroxyapatite bone repair material of the present invention can be used as a composite scaffold to load different types of drugs, such as bone morphogenetic protein-2, to improve the biological activity of the scaffold and significantly enhance the osteogenic induction ability, so that the scaffold can be used as a drug carrier to achieve a sustained drug release effect, becoming an ideal bone repair scaffold material.
[0017] (5) The high-strength silk fibroin / hydroxyapatite bone repair material of the present invention has good biocompatibility and biodegradability as the raw materials, is low in cost, simple to operate, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 : H NMR spectra of silk fibroin and methacrylated silk fibroin.
[0019] Figure 2 : Infrared spectra of nanohydroxyapatite, 2-hydroxyethyl methacrylate and methacrylated nanohydroxyapatite.
[0020] Figure 3 : Scanning electron microscopy images of the interface between methacrylated silk fibroin and (A) nanohydroxyapatite and (B) methacrylated nanohydroxyapatite.
[0021] Figure 4 : Comparison of compression modulus of silk fibroin / hydroxyapatite bone repair materials prepared with different contents of nanohydroxyapatite or methacrylated nanohydroxyapatite.
[0022] Figure 5 : Release curves of BMP-2 drug in silk fibroin / hydroxyapatite bone repair materials under different pH environments. DETAILED DESCRIPTION
[0023] In order to verify the feasibility of the design, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the application of the present invention is not limited to this.
[0024] Example 1 (1) Preparation of methacrylated silk fibroin solution: 3 L of deionized water was boiled and 15.9 g of anhydrous sodium carbonate was added. After the sodium carbonate was fully dissolved, 60 g of silk was weighed and placed in the solution. The solution was degummed at 100 °C for 30 min. The boiled silk was taken out and washed thoroughly with deionized water. The degummed silk was dried in an oven at 60 °C to obtain degummed silk. 40 g of the dried degummed silk was added to 200 mL of 9.3 M LiBr solution and dissolved at 60 °C for 1 h to obtain a silk fibroin / lithium bromide mixed solution. Subsequently, 12 mL of glycidyl methacrylate was added and stirred at 60 °C in the dark for 3 h. After the reaction was completed, the solution was transferred to a dialysis bag with a molecular weight cutoff of 8000-14000 Da and dialyzed with deionized water for 5 days. The dialysis process was kept away from light. The dialyzed solution was centrifuged and concentrated to obtain a methacrylated silk fibroin solution with a mass fraction of approximately 25%.
[0025] (2) Preparation of methacrylated nanohydroxyapatite: 10.5 g of nanohydroxyapatite was placed in an oven at 120°C to dry to remove moisture. 10 g of dried nanohydroxyapatite and 5 mL of isophorone diisocyanate were added to a three-necked flask and sealed, then heated and stirred in an oil bath at 50°C. 0.5 mL of dibutyltin dilaurate and 300 mL of N,N-dimethylformamide were added to the flask and nitrogen was introduced. After reacting for 48 h, 6 mL of 2-hydroxyethyl methacrylate was added and stirring continued for 8 h. 100 mL of methanol was then added to terminate the reaction. The precipitate was collected by centrifugation, washed with dichloromethane, dried at room temperature for 48 h, and then ground into powder to obtain methacrylated nanohydroxyapatite.
[0026] (3) Preparation of silk fibroin / hydroxyapatite cross-linking system: Add 0.3% by mass of phenyl-2,4,6-trimethylbenzoyl lithium hypophosphite (LAP) to 1 mL of 25% by mass of methacrylated silk fibroin solution, and then add 10 wt% by mass of methacrylated nanohydroxyapatite powder. Stir and mix evenly at room temperature in the dark to obtain a precursor slurry of bone repair material; irradiate the precursor slurry under 365 nm ultraviolet light for 10 min to obtain a silk fibroin / hydroxyapatite cross-linking system.
[0027] (4) Preparation of high-strength silk fibroin / hydroxyapatite bone repair material: The prepared silk fibroin / hydroxyapatite cross-linked system was freeze-dried at -80°C for 24 hours and then crushed into powder using a high-speed crusher at a speed of 39,000 r / min for 30 minutes. The powder was hot-pressed at a pressure of 2 MPa and a temperature of 200°C for 20 minutes to obtain a high-strength silk fibroin / hydroxyapatite bone repair material.
[0028] like Figure 1 As shown, the methacrylated silk fibroin prepared in this example has characteristic peaks of methacrylate vinyl (δ = 6.2-6 ppm and 5.8-5.6 ppm) and methyl (δ = 1.8 ppm) in the glycidyl methacrylate molecule, which proves the chemical modification of silk fibroin by glycidyl methacrylate and the successful preparation of methacrylated silk fibroin.
[0029] like Figure 2 As shown in the infrared spectrum, the methacrylated nanohydroxyapatite prepared in this embodiment showed a characteristic peak of 2-hydroxyethyl methacrylate (2940 cm -1 -CH2 group at 1640 cm -1 The C=C group at the end of the reaction mixture indicates the successful synthesis of methacrylated nanohydroxyapatite.
[0030] Example 2 Except that the mass fraction of the methacrylated nano-hydroxyapatite powder added in step (3) is changed to 30 wt %, the other steps are the same as those in Example 1.
[0031] Example 3 Except that the mass fraction of the methacrylated nano-hydroxyapatite powder added in step (3) is changed to 50 wt %, the other steps are the same as those in Example 1.
[0032] Comparative Example 1 Except for adding nano-hydroxyapatite powder that has not been methacrylated in step (3), the other steps are the same as those in Example 1.
[0033] Comparative Example 2 Except for adding nano-hydroxyapatite powder that has not been methacrylated in step (3), the other steps are the same as those in Example 2.
[0034] Comparative Example 3 Except for adding nano-hydroxyapatite powder that has not been methacrylated in step (3), the other steps are the same as those in Example 3.
[0035] like Figure 3 As shown, from Figure 3(A) It can be seen that in the bone repair material prepared using unmodified nanohydroxyapatite in Comparative Example 1, the hydroxyapatite is largely aggregated within the silk fibroin network and is not evenly dispersed. In contrast, as can be seen in Figure 3 (B), in the bone repair material prepared using methacrylate-modified nanohydroxyapatite in Example 1, the hydroxyapatite does not aggregate, is evenly dispersed within the silk fibroin network, and tightly adheres to the inner walls of the pores of the silk fibroin scaffold, demonstrating good bonding and dispersion between the silk fibroin and hydroxyapatite.
[0036] like Figure 4 As shown, a comparison of the compression modulus reveals that, at the same inorganic content, the compression modulus of the methacrylated nanohydroxyapatite group is significantly greater than that of the unmodified nanohydroxyapatite group. The compression modulus of the silk fibroin / hydroxyapatite bone repair material prepared in Comparative Example 3 is 17.08 MPa, which is significantly lower than the compression modulus of the silk fibroin / hydroxyapatite bone repair material prepared in Example 3 (46.33 MPa). These results indicate that compared to nanohydroxyapatite that has not been methacrylated, the bone repair material prepared using methacrylated nanohydroxyapatite significantly improves the mechanical properties of the bone repair material.
[0037] Comparative Example 4 Step (1) and step (2) are the same as in Example 3; (3) Preparation of silk fibroin / hydroxyapatite bone repair material: Add 0.3% by mass of phenyl-2,4,6-trimethylbenzoyl lithium hypophosphite (LAP) to 1 mL of 25% by mass of methacrylated silk fibroin solution, and then add 50 wt% by mass of methacrylated nanohydroxyapatite powder. Stir and mix evenly at room temperature in the dark to obtain a precursor slurry of bone repair material; irradiate the precursor slurry under 365 nm ultraviolet light for 10 min to obtain silk fibroin / hydroxyapatite bone repair material.
[0038] The compression modulus of the silk fibroin / hydroxyapatite bone repair material prepared by the above steps in this comparative example 4 is 12.69 MPa, which is significantly lower than the compression modulus (46.33 MPa) of the silk fibroin / hydroxyapatite bone repair material prepared in Example 3. The above results show that in Example 3, the powder prepared by vacuum freeze-drying and grinding the covalently cross-linked silk fibroin / hydroxyapatite cross-linking system at -80°C is hot-pressed at a pressure of 2 MPa and a temperature of 200°C for 20 minutes, which is conducive to the interface fusion between the organic component silk fibroin and the inorganic component hydroxyapatite in the composite material, forming a high-strength silk fibroin / hydroxyapatite bone repair material with a uniform and complete interface, thereby significantly improving the mechanical properties of the bone repair material.
[0039] Application Example 1 Step (1) and step (2) are the same as in Example 1; (3) Preparation of silk fibroin / hydroxyapatite crosslinking system: Add 0.3% by mass of phenyl-2,4,6-trimethylbenzoyl lithium hypophosphite (LAP) to 1 mL of 25% by mass of methacrylated silk fibroin solution, and then add 10 wt% by mass of methacrylated nanohydroxyapatite powder. Stir and mix evenly at room temperature in the dark to obtain a precursor slurry of bone repair material. Add 3 μg / mL of bone morphogenetic protein-2 (BMP-2) drug to the solution and stir and mix evenly. Finally, the obtained bone repair material precursor slurry containing BMP-2 drug was irradiated under 365 nm ultraviolet light for 10 min to obtain a silk fibroin / hydroxyapatite crosslinking system loaded with BMP-2 drug.
[0040] (4) Preparation of high-strength silk fibroin / hydroxyapatite bone repair material: The prepared silk fibroin / hydroxyapatite cross-linked system was freeze-dried at -80°C for 24 hours and then crushed into powder using a high-speed crusher at a speed of 39,000 r / min for 30 minutes. The powder was hot-pressed at a pressure of 2 MPa and a temperature of 200°C for 20 minutes to obtain a high-strength silk fibroin / hydroxyapatite bone repair material.
[0041] like Figure 5 As shown, the high-strength silk fibroin / hydroxyapatite bone repair material loaded with BMP-2 can slowly release BMP-2. The above results confirm that the high-strength silk fibroin / hydroxyapatite bone repair material can be used as a drug sustained-release carrier to continuously release the loaded drug and improve the biological activity of the material.
[0042] The above descriptions are merely embodiments of the present invention. All equivalent changes and modifications made within the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material, characterized in that: Methacrylated silk fibroin and methacrylated nano-hydroxyapatite are mixed, covalently cross-linked under the action of a photoinitiator, and then subjected to high-temperature hot pressing to obtain a high-strength silk fibroin / hydroxyapatite bone repair material.
2. The method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material according to claim 1, characterized in that: The specific steps include: (1) Preparing a methacrylated silk fibroin solution: heating deionized water to boiling, adding anhydrous sodium carbonate and silk to degumming the silk; after washing and drying, dissolving the dried degummed silk in a lithium bromide solution to obtain a silk fibroin / lithium bromide mixed solution, then adding glycidyl methacrylate to modify the silk fibroin in the dark for 3 hours, then dialyzing the silk fibroin with deionized water at room temperature in the dark for 5 days, centrifuging the dialyzed solution, and concentrating the solution to obtain a methacrylated silk fibroin solution; the mass fraction of the methacrylated silk fibroin solution is 15%-30%; (2) Preparation of methacrylated nanohydroxyapatite: The dehydrated nanohydroxyapatite and isophorone diisocyanate are heated and stirred in an oil bath, followed by addition of dibutyltin dilaurate and N,N-dimethylformamide, and the reaction is carried out in a nitrogen environment, followed by addition of 2-hydroxyethyl methacrylate and continued stirring, and finally, methanol is added to terminate the reaction; the precipitate is collected by centrifugation, washed with dichloromethane, dried at room temperature, and ground to obtain methacrylated nanohydroxyapatite powder; (3) Preparing a silk fibroin / hydroxyapatite crosslinking system: mixing the methacrylated silk fibroin solution obtained in step (1) with a photoinitiator, and then adding the methacrylated nano-hydroxyapatite powder obtained in step (2), stirring and mixing at room temperature in the dark to obtain a precursor slurry of a bone repair material; irradiating the precursor slurry under ultraviolet light to obtain a silk fibroin / hydroxyapatite crosslinking system; (4) Preparation of high-strength silk fibroin / hydroxyapatite bone repair material: The silk fibroin / hydroxyapatite cross-linking system prepared in step (3) was freeze-dried in vacuum at -80°C, and then crushed and ground into powder using a high-speed crusher at a speed of 39,000 r / min. The powder was hot-pressed at a pressure of 2 MPa and a temperature of 200°C for 20 minutes to obtain a high-strength silk fibroin / hydroxyapatite bone repair material.
3. The method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material according to claim 2, characterized in that: The reaction temperature for adding 2-hydroxyethyl methacrylate and continuing stirring in step (2) is 40-80° C., the reaction time is 1-5 h, and the reaction is carried out in the dark.
4. The method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material according to claim 2, characterized in that: The mass fraction of the methacrylated nano-hydroxyapatite powder in the precursor slurry of the bone repair material in step (3) is 10wt% - 50wt%.
5. The method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material according to claim 2, characterized in that: The photoinitiator in step (3) is one of Irgacure 2959, Ruthenium Photoinitiator and phenyl-2,4,6-trimethylbenzoyl lithium hypophosphite.
6. The method for preparing a high-strength silk fibroin / hydroxyapatite bone repair material according to claim 2, characterized in that: The wavelength of the ultraviolet light in step (3) is 365 nm, and the irradiation time is 5-20 min.
7. A high-strength silk fibroin / hydroxyapatite bone repair material prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the high-strength silk fibroin / hydroxyapatite bone repair material for loading drugs as claimed in claim 7, characterized in that: The drug is added to the precursor slurry of the bone repair material.
Citation Information
Patent Citations
Silk fibroin / hydroxyapatite composite scaffold and preparation method thereof
CN110522950A
High mechanical strength silk fibroin-hydroxyapatite composite bone scaffold and its preparation method
CN112972766B
Hydroxyapatite / chitosan-silk fibroin nanocomposite and preparation method thereof
CN102085391A
Injectable silk fibroin bone repair filling sustained-release material, and preparation method and application thereof
CN103041447A
SILK FIBROIN / HYDROXYAPATITE COMPOSITE MATERIAL, ITS PRODUCTION METHOD, AND ITS APPLICATION
RU2023122197A
Cited By
Preparation method of full-time controllable water-absorbing material and flow-state solidified soil building material prepared from full-time controllable water-absorbing material
CN121085573A
A method for preparing a water-absorbing material with all-time controllable properties and its fluidized solidified soil building material
CN121085573B
Silk fibroin-copper ion complex modified polymethyl methacrylate based bioactive bone cement and preparation method thereof
CN122516437A